Patterns of Secularization and Religious Rationalization in Emile Durkheim and Max Weber - Goldstein, Warren S. (Implicit religion, 2009)
Emile Durkheim's and Max Weber's sociologies of religion contain three different patterns of secularization and religious rationalization: the unilinear, the dialectical, and the nonlinear (which includes the paradoxical). Based on an analysis of Durkheim's and Weber's writings on religion, this paper argues that the process of religious rationalization and secularization is not always linear but can also take place in a dialectical or paradoxical manner. Whereas in the unilinear and dialectical theories of religious rationalization and secularization there is a progressive development, in the nonlinear or paradoxical theory, development is arrested. While the unilinear and dialectical theories are associated with the Occidental development to modernity, the paradoxical nature of theoretical religious rationalization was characteristic ofthe "arrested" development ofthe Orient, while the paradoxical aspects ofsecularization are associated with unresolved contradictions of modernity (the postmodern).